Estimating missing data in air pollution data using interpolation technique: effects on fitting Gamma Distribution - Norazian, Mohamed Noor; Mohd Mustafa, Al Bakri Abdullah; Ahmad Shukri, Yahaya; Nor Azam, Ramli (Universiti Sains Malaysia (USM) & Malaysian Mathematical Sciences Society, 2008)
Organized by Universiti Sains Malaysia (USM) & Malaysian Mathematical Sciences Society, 5th - 6th December 2007 at The Gurney Hotel, Penang.